Studi Kualitas Pelayanan Publik di Kantor Kecamatan Leihitu Barat, Kabupaten Maluku Provinsi Maluku - Tuhelelu, Nurul Fatah; Selanno, Hendry; Patty, Julia Theresia (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
This study aims to explain and analyze the quality of public services at the Leihitu Barat District Office. Quality public service is a key indicator in assessing the performance of local governments, particularly at the sub-district level, which directly provides services to the community. This research uses a descriptive method with a qualitative approach to gain an in-depth understanding of the current service conditions. The informants in this study totaled 10 people, consisting of district officials and community members who use the services. Data were collected through in-depth interviews, observations of service activities at the sub-district office, and documentation of relevant supporting documents. The collected data were analyzed using descriptive qualitative analysis with a case study approach, providing a comprehensive picture of existing problems and potentials. The assessment of service quality is based on Zeithaml’s theory, which includes five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research findings indicate that the quality of public services at the Leihitu Barat District Office has not yet met optimal standards. In terms of tangibles, it was found that physical facilities such as waiting areas, service desks, and supporting equipment are still very limited. The reliability dimension is also not well fulfilled, as the service processes are often inconsistent and not timely. The assurance dimension reflects a lack of professional ability and attitudes among officials in providing a sense of security and trust to the public. However, the dimensions of responsiveness and empathy show relatively positive developments. Some officials have demonstrated responsive and empathetic attitudes in addressing the needs and complaints of the public. Nonetheless, comprehensive improvements are still necessary. These include enhancing the quality of human resources, increasing the availability of physical infrastructure, and improving service management systems. By addressing these areas, public services at the Leihitu Barat District Office can become more effective and better aligned with community expectations.